Economic feasibility of weed management practices in nigella (Nigella sativa L.) - R L Meena, D K Sharma, S S Meena, R S Mehta, R D Meena, (Journal of Spices and Aromatic Crops, 2014)
A field experiment was conducted to find out the suitable and economical method of weed control in nigella. Based on two year study, it was found that besides weed free treatment, significantly higher plant height, number of primary and secondary branches, number of leaves, number of nodes and dry matter accumulation plant-1 (at 60 days after sowing (DAS), 90 DAS and at harvest) were recorded with the pre-emergence application of oxadiargyl @ 75 g ha-1 + one hand weeding at 45 DAS and pendimethalin @ 1 kg ha-1 + one hand weeding at 45 DAS. Similarly, yield attributes like number of siliqua plant-1, number of seeds siliqua-1, siliqua size and test weight as well as seed and straw yields of nigella were also higher with these two treatments. Besides weed free treatment, lower dry weight of weed at harvest, weed index with highest weed control efficiency was obtained under pre- emergence (PE) application of oxadiargyl @ 75 g ha-1 + one hand weeding at 45 DAS. The Highest gross returns and net returns were obtained in weed free treatment followed by effective control of weed with pre -emergence application of oxadiargyl @ 75 g ha-1 + one hand weeding at 45 DAS but highest B: C ratio (2.62) was recorded with preemergence application of oxadiargyl @ 75 g ha-1 + one hand weeding at 45 DAS.